Exploring the Social Functions of Language and Its Relationship with Society Among English Major Students - Jumarizah, Andi Astuti; Walianna, Andi Bunga; Rahayu, Sri; Bustan, Sri Rezki (Journal of Language Learning and Assessment, 2025)
Purpose This study aims to identify and analyze the main functions of language in social interactions and to explain the relationship between language and society as perceived by English department students. Methodology The research employs a qualitative approach with Halliday’s theory of language functions and the sociolinguistic perspectives of Wardhaugh and Holmes as its theoretical framework. Data were collected through observations and interviews with students to understand language use in social contexts and the influence of social factors on their language practices. Results/Findings The findings reveal that students use various language functions such as expressive, informative, and interactional according to social context, but their awareness of sociolinguistic factors remains limited. This emphasizes that mastery of linguistic forms alone is insufficient without understanding the social contexts that influence language use. Implications The practical implication of this research encourages enhancing the English language curriculum by incorporating awareness of language functions and social factors in order to develop students’ communicative competence more comprehensively and effectively in various social situations.